Implementasi Program Sekolah Siaga Bencana di Smp Negeri Padureso Kabupaten Kebumen - Oktafiani, Ika Nur; Aji, Ananto (Edu Geography, 2019)
Land slide disaster that happened several times in SMP NegeriPadureso and giving effect to the school building and make that school become the most potentially land slide disaster school in PaduresoSubdistrict. Purpose of this research is to measure student knowledge, analyze the implementation of preparedness disaster school, and analyze obstacle of that program in SMP Negeri Padureso. Sample interpretation technique that used is total sampling with amount of student on 8th and 9th grade is 103 that have been followed socialization and simulation of preparedness to face disaster in SSB program. Data interpretation technique that used is observation, interview, test, quesionery, and documentation. Data analysis technique that used is descriptive statistic with quantitative approach. The result of this research shows that : a) level of student knowledge is need to be increased in any indicator because its still low, b) result about analysis SSB program, c) the obstacle is internal obstacle about fund, school society awareness, and there is no SOP and curriculum of SBB. Bencana tanah longsor yang sering terjadi dan mengakibatkan beberapa kerusakan di lingkungan sekolah menjadikan SMP Negeri Padureso menjadi sekolah paling berpotensi terhadap bencana tanah longsor di Kecamatan Padureso. Tujuan penelitian ini mengukur pengetahuan siswa, menganalisis implementasi program sekolah siaga bencana, dan menganalisis kendala program sekolah siaga bencana di SMP Negeri Padureso. Teknik pengambilan sampel yaitu total sampling dengan jumlah 103 siswa kelas VIII dan IX yang telah mengikuti sosialisasi dan simulasi kesiapsiagaan menghadapi bencana dalam program SSB. Teknik pengambilan data berupa observasi, wawancara, test, kuesioner, dan dokumentasi. Teknik analisis data menggunakan analisis statistik deskriptif dengan pendekatan kuantitatif. Hasil penelitian ini yaitu: a) tingkat pengetahuan siswa perlu ditingkatan di beberapa indikator karena masih tergolong rendah, b) analisis implementasi program SSB, c) kendala yang dihadapi adalah kendala internal berupa dana, kesadaran warga sekolah, belum adanya SOP dan kurikulum SSB.